(untitled) (Cultura Económica, 2018)
The author argues that searching for new models for business functioning and economic policy invites us to rediscover the personalist philosophy of Jacques Maritain. At the core of Maritain’s Humanisme Intégral (1936) is the idea that man is a person who is "spiritual in nature, endowed with free will, and thus autonomous in relation to the world". The paper studies temporal common good’s inner nature, that according to Maritain concerns the good life of the entire community —the common good or bonum commune— both in the material and moral sense. This bonum commune is not the ultimate goal of the temporal order, but it is subordinate to what transcends temporal welfare of the human person—the attainment of freedom and spiritual perfection. In the end, this temporal order is never completed. The definitive balance or telos is never obtained because man is always on the path.